Implications potentielles de l’utilisation de l’information génétique numérique sur les ressources génétiques sur les trois objectifs de la Convention sur la diversité biologique. Document soumis par le CGIAR au Secrétariat de la Convention sur la diversité biologique - Halewood, Michael; López Noriega, Isabel; Ellis, David; Roa, C.; Rouard, M.; Sackville-Hamilton, N. Ruaraidh (2017)
This report has been submitted by CGIAR in response to an invitation issued by the Secretary of the Convention on Biological Diversity (CBD) calling on “relevant organizations and stakeholders to submit views and relevant information on any potential implications of the use of digital sequence information on genetic resources for the three objectives of the Convention” as input to the "Meeting of the Ad Hoc Technical Expert Group on Digital Sequence Information on Genetic Resources", 13 - 16 February 2018, Montreal, Canada. CGIAR experience to date confirms that digital genomic sequence data can play important roles in the management and sustainable use of biological diversity and in the sharing of benefits associated with the use of that diversity. Technological capacities to generate genomic sequence data have accelerated faster than capacities to enable practical use of this information. Relatively small investments in the initial generation of genomic sequences, must then be coupled with significantly larger investments to comparatively analyse genomic sequences, to link genetic variability to useful phenotypic traits or performance, to ‘optimize’ those traits, and ultimately, to develop new crop varieties for release and use in farmers’ fields. CGIAR underscores the importance of capacity building for developing country research and development organizations to generate and use genomic sequence information as part of their own conservation and crop improvement programs, and to be able to participate on equal footing in internationally coordinated and funded research and development programs. The most important benefit to be shared from the use of genomic sequence information in agricultural research and development and plant breeding is improved food and livelihood security. Other non-monetary benefits are farmers’ improved access to technologies, enhanced institutional capacities of developing country research organizations, shared research results, and local and regional economic development.